2008
DOI: 10.1016/j.biopsych.2008.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Classification of White Matter Lesions on Magnetic Resonance Imaging in Elderly Persons

Abstract: White matter lesions, commonly seen on magnetic resonance images of elderly people, are related to various geriatric disorders including cerebrovascular diseases, cardiovascular diseases, dementia, and psychiatric disorders. Currently, white matter lesions are divided into periventricular white matter lesions and deep white matter lesions. Although the meaning of these terms vary by study and this dichotomization itself is still in debate, a possible dissimilarity in pathogenic mechanisms between periventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
454
4
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(486 citation statements)
references
References 94 publications
(115 reference statements)
15
454
4
13
Order By: Relevance
“…3 Vascularrelated changes are usually associated with high-grade DWMHs, whereas non-ischemic age-related changes are usually related to PVHs. 3,16 Specifically, the diagnosis of arterial hypertension was related to high-grade DWMHs in our sample. Only severe PVHs extending to deep WM are clearly vascular-related changes, but none of our participants with high-grade PVHs were rated with severe lesions.…”
Section: Discussionmentioning
confidence: 81%
“…3 Vascularrelated changes are usually associated with high-grade DWMHs, whereas non-ischemic age-related changes are usually related to PVHs. 3,16 Specifically, the diagnosis of arterial hypertension was related to high-grade DWMHs in our sample. Only severe PVHs extending to deep WM are clearly vascular-related changes, but none of our participants with high-grade PVHs were rated with severe lesions.…”
Section: Discussionmentioning
confidence: 81%
“…Also, the u-fibers are frequently spared in the case of widespread whitematter lesions. 23 Enlarged PVSs are a common finding in the white matter, especially in the context of CAA. 24 In our study, MR identified 'lesions' in juxtacortical areas that had similar appearance as intracortical CMIs proved to be PVSs on histology.…”
Section: Discussionmentioning
confidence: 99%
“…Peri-Ventricular Hyperintensity (PVH) as the name connotes refers to homogenous high signals contiguous to lateral ventricles on T2 weighted (T2W), Fluid Attenuated Inversion Recovery (FLAIR), and Proton Density (PD) images, without prominent hypointensity on T1 weighted (T1W) MR images [1][2][3][4][5]. They are differentiated from infarcts as they are not usually evident on T1W MR images and they do not follow specific vascular territories [2].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Geriatric disorders like cerebrovascular diseases (CVD), cardiovascular diseases and Dementia, [4]. [3][4][5]9,11,[17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation